Constitutional Irregularities in the British Imperial Courts of Vice Admiralty during the Mid-Nineteenth Century. Issue 2 (3rd May 2016) - Marten, Bevan
ABSTRACT: During the mid-nineteenth century there were between forty and fifty courts of vice admiralty located in colonies across the British empire. They were imperial institutions, whose officers were supposed to be appointed by the High Court of Admiralty in London. However, the complexity and obscurity of the official process, combined with the lack of priority given to the courts by imperial and colonial officials alike meant that many of these courts experienced unfilled vacancies and irregular appointments. This article discusses the shortcomings of the vice admiralty system that gave rise to these irregularities, and led to the passage of the Vice Admiralty Courts Act in 1863. It demonstrates that the courts were ineffective instruments of imperial authority, and that by the time the 1863 Act was passed their integration into the regular colonial courts was inevitable.